PENERAPAN DAN PEMANFAATAN TAKSONOMI UNTUK MENDAYAGUNAKAN FAUNA DAERAH - Soenartono - Adisoemarto (ZOO INDONESIA, 2006)
Adisoemarto, S. 2006.The application and utilization of taxonomy for the localfauna values. Zoo Indonesia vol. 15 (2): 87-100. Taxonomy is the way of mankindlooking to any living things within their environment in a small scale and the wholeliving things in a large scale. From the taxonomical process will derive some results,one of them is the scientific names.